Indeksasi Moderasi Beragama Berbasis PCA di Perguruan Tinggi Keagamaan Islam - Kusumawardani, Rizky (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2023)
This article aims to fill the void of the index of religious moderation at the UIN Raden Mas Said Surakarta, a need that has not been met despite efforts to cultivate the values of religion's moderation every year. The study used the Principal Component Analysis (PCA) method to develop a religious moderation index based on data from 39 measured, valid, and reliable indicators, taken from 591 student samples. The index is formed from a single principal value with a weighting interval between 0.08 and 0.184. The results of the study result in a religious moderation index with a value interval between 6.16 and 43.16. Advanced analysis shows that moderation of UIN students Raden Mas Said Surakarta tends toward moderation. The research has made important contributions to understanding the conditions of religious moderation among students and related disciplines, as well as providing a foundation for the development of strategies for religious Moderation in the academic community.